Program Kegiatan dan Penerapan New Normal Untuk Meningkatkan Kesadaran Masyarakat Terhadap Pencegahan Covid-19 di Kelurahan Kampung Tengah - Peggi Muharrani Gusti; Neni Hermita; Jesi Alexander Alim; Lenni Taniya Nainggolan; Rika Cintya Napitupulu; Jeri Juliandi; M. Aditya (Journal of Community Engagement Research for Sustainability, 2021)
Real work lectures are a form of student service to the community as a manifestation of the tri dharma of higher education. In this period, the actual work lecture activities underwent a change in the procedure in which the kukerta activities were carried out at the student's residence. This is because the spread of the Covid-19 virus is increasing day by day. This activity aims to make students able to appreciate and overcome problems that arise in a society that is generally complex, as well as to help prevent the spread of the Covid-19 Virus. The ease in dealing with this is carried out systematically and is reflected in student activities when carrying out the Covid-19 Volunteer Kukerta programs in the Kelurahan. The Covid-19 Volunteer Kukerta activity at the University of Riau was carried out in Kampung Tengah Village, Sukajadi District, Pekanbaru City, Riau. The Covid-19 Kukerta Volunteer Team at the University of Riau runs various programs that support the prevention and control of the Covid-19 outbreak, including the program for making and distributing hand sanitizers, spraying disinfectant programs, making and distributing herbal medicine programs, mutual cooperation program activities, and the Riau Bank cash social assistance program Riau Islands, and the food distribution program.